CONDITIO SINE QUA NON: Humanism In Al Firdaus Inclusive Middle School Surakarta - Indri Indri (Universitas Sebelas Maret, 2024)
This study aims to explore the practice of humanism in education through a phenomenological case study at Al Firdaus Middle School (SM) Surakarta. The findings reveal that the school's humanistic approach is embodied in its thematic learning evaluations, especially for students with special needs (anak berkebutuhan khusus/ABK). Key practices include the presence of special assistant teachers (GPK), implementation of individual learning programs (PPI), early and continuous student assessments, and differentiated general test (GT) formats regular, substitution, omission, and modification tailored to each student’s ability. Additional components include presentation-based assessments, full parental participation through screening processes, cooperative learning strategies, and remedial instruction rooted in repeated learning activities. Notably, students with special needs are fully integrated into regular classes, fostering inclusive education. The research argues that such practices restore education to its core/khittah its true path of humanizing learners. In contrast, dehumanizing education strips education of its essence and purpose. Humanism in education understood as humanizing students is an undeniable necessity, or conditio sine qua non, for meaningful learning. First, students must be subjects, not objects, of education; they must occupy a central role in shaping educational direction. Second, diversity in harmony must be upheld as a foundational educational principle. Third, educators must minimize